INFLUENCE OF THE RAIL SLOPE ON THE NATURE OF THE CONTACT INTERACTION AND THE STRESS-DEFORMED CONDITION OF THE RAIL IN RAIL TRACK (Transport systems and technologies, 2018)
Studies carried out on the roads of the Kiev Metro have shown that the number of defects of contact-fatigue origin, the appearance of which leads to a reduction in the length of operation of railways rails, tends to increase. Despite numerous research of the wheel-rail interaction [3-8] and efforts to optimize the specified contact pair, many issues remain uncertain. Using the finite element method, authors simulated the interaction of rails with wheels of rolling stock in a railway track.The geometry of the surface of the rails corresponded to the types of rails P50, P65 and UIC60, the slopes of the rails were taken equal to 0, 1:20 and 1:40 on concrete sleepers with a diagram of 1680 pc/km (inter-span distance 60 cm). The axle load on the rolling stock wheel for all variants of the calculations was the same and was 75 kN, which corresponds to the load on the axle equal to 150 kN. The tasks were solved in an elastic setting.The results of the conducted mathematical modeling showed that with the location of the rails in the straight section of the track and the use of rolling stock with the type of wheels used in the calculations, the profile of the rails P50 and P65 is the most optimal in terms of reducing the contact stresses with a 1:20 slip . When slipping 1:40 rails, the profile of the UIC60 rail is more optimal. The absence of a slope of the rail leads to an increase in the levels of contact interaction forces, with the level of equivalent stress almost equal for all profiles of rail in track.
Keywords: rail, wheel, contact stresses, finite element method